EDITORIAL. (7th February 2013) - Lees, Christoph
Abstract : I thank Steve Robson and his team of Editors for their very hard work over the previous years in establishing Fetal and Maternal Medicine Review ( FMMR ) as a reference point for authoritative reviews in the field of perinatology. I am delighted that Steve is staying on as an Associate Editor, and am very pleased to welcome Professor Neil Sebire (UK) and Professor Jimmy Espinoza (USA) as Associate Editors for 2013 issues onwards. Amanda Johns has taken over from Jean Birtles in the Editorial Office and can be contacted by email atfmr_editorial_office@cambridge.org .